Hydroxyapatite granules for the surgical treatment of calcaneal intraosseous lipomas: A case report - Amit Chandrakant Supe; Chandrashekhar Martand Badole; Kiran Narayanrao Wandile (Wolters Kluwer Medknow Publications, 2016)
Intraosseous lipoma of calcaneus is a rare occurrence. It is a benign tumor and frequently associated with pain in heel. Diagnosis can be done by a biopsy of the lesion. This tumor can be treated with curettage and filling cavity with hydroxyapatite granules. We present a case of intraosseous lipoma treated with curettage and hydroxyapatite granules.